1997
DOI: 10.1016/s0029-7844(96)00510-8
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic screening to detect fetal cardiac anomalies: A 5-year experience with 111 abnormal cases

Abstract: The sensitivity of sonographic screening to defect fetal cardiac anomalies varies with the type of lesion. Isolated septal defects are the most difficult lesions to detect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 19 publications
2
28
0
6
Order By: Relevance
“…Unfortunately, most population studies regarding the use of ultrasonography to detect congenital heart disease have reported low sensitivities for abnormalities of the great arteries [10,12,13,28,41,42,63,64]. Studies documenting higher detection rates emphasized routine visualization of the outflow tracts in addition to the usual four-chamber view [8,22,24,25,27,32,36,37,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most population studies regarding the use of ultrasonography to detect congenital heart disease have reported low sensitivities for abnormalities of the great arteries [10,12,13,28,41,42,63,64]. Studies documenting higher detection rates emphasized routine visualization of the outflow tracts in addition to the usual four-chamber view [8,22,24,25,27,32,36,37,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 2 decades considerable clinical and teaching efforts have been made to incorporate a second-trimester fetal ultrasound screening for congenital malformations, including basic heart assessment, into routine prenatal care. However, this cardiac scan has not been performed uniformly; while some have limited it to the 4-chamber view, others have added the visualization of the outflow tracts, and this has significantly affected the prenatal detection rates of CHD [11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…[1][2][3][4][5] However, even with an antenatal diagnosis, some fetuses with TGA will have profound hypoxemia and may even die in the neonatal period as a result of a restrictive foramen ovale, ductus arteriosus constriction, or pulmonary hypertension. 6 -11 The goal of our study was to determine whether prenatal echocardiography can identify these high-risk fetuses with TGA.…”
mentioning
confidence: 99%